Valuation of O2 Czech Republic a.s. - Stehno, Josef; Tyll, Ladislav; Sieber, Patrik, 1977-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
Thesis aims to assess the value of the company O2 Czech Republic a.s. to the date 29th of June 2018 and based on determined enterprise value sets a goal share price for potential investors. The valuation is conducted from the position of an external analysis and no internal or otherwise publicly not available data are used. Theoretical part of thesis includes a brief overview of different applicable valuation methods and introduces a general approach to company valuation based on which builds the practical part of thesis. In practical part of thesis is conducted an analysis of telecommunication industry in which O2 Czech Republic a.s. operates, complemented with financial analysis of company with focus on comparison to its competitors. Valuation part of the thesis is built on two valuation methods, first the intrinsic valuation method based on DCF model and as a supportive relative valuation based on multiples method. The final output of valuation is comparison of valuation results with the current O2 CZ share market price and investment recommendation.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses